Public Perception on Reintegration of Captive Farmers Returnees by Boko Haram Insurgents in Borno State: Evidence from Dikwa Local Government Area - Ahmed, Jaji (Pancasila International Journal of Applied Social Science, 2024)
This study assessed the community perception on the reintegration of captive farmers returnees of Boko Haram insurgency in Borno State, Nigeria, with specific reference to Dikwa Local Government Area. The study adopted a mixed-methods approach, combining quantitative and qualitative data collection and analysis. The study population consisted of 300 captive farmer returnees, 100 community members, and 20 key informants from the authorities and civil society organizations. The study used a stratified random sampling technique to select 150 captive farmer returnees, 50 community members, and 10 key informants for the survey. The study also conducted 10 focus group discussions and 10 in-depth interviews with the selected respondents. The study found that the reintegration of captive farmer returnees was necessary and justified for the peace and security of the area, as well as for the restoration of the livelihoods and dignity of the returnees. However, the study also found that the role of the authorities in facilitating the reintegration of captive farmer returnees was mixed and inadequate, and that there were several challenges and gaps in the coordination, management, and implementation of the reintegration program. Moreover, the study found that the reintegration of captive farmer returnees faced various challenges, such as stigma and discrimination, trauma and psychological distress, poverty and unemployment, insecurity and fear, and lack of trust and confidence. The study concluded that the reintegration of captive farmer returnees by Boko Haram insurgents in Dikwa Local Government Area Borno State was a necessary but challenging process, and that the role of the authorities and the perception of the communities were critical factors for the success and sustainability of the reintegration program. The study recommended that the authorities should improve the coordination and collaboration, enhance the transparency and accountability, provide adequate security and protection, provide basic services and amenities, provide psychosocial support and counseling, provide vocational training and income-generating activities, and provide legal assistance and documentation for the returnees and the communities. The study also recommended that the communities should accept and welcome the returnees, support and assist the returnees, engage and cooperate with the authorities and the reintegration program, and foster a culture of peace and tolerance in the area.